2022
DOI: 10.1177/00219983221101220
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stacking sequence of glass and jute fiber reinforced polymer composites on their low velocity impact properties

Abstract: This paper investigated the effect of stacking sequence on the low velocity impact behavior of glass and jute fiber reinforced hybrid composites. The hand layup method is used to fabricate the composites with various stacking sequences. The low velocity impact analysis was carried out at various impact energies, namely 5 J, 10 J and 15 J. Dye penetrant inspection (liquid penetrate inspection) was performed to analyses the damage area in the composites. Compression after impact (CAI) testing was conducted to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…They observed that the jute fiber/epoxy specimen has the highest damaged area compared to glass fiber/epoxy and carbon fiber/epoxy specimens. The effect of stacking sequence on the low‐velocity impact and compression after impact behavior of glass and jute fiber reinforced hybrid composites was investigated by Pandian et al, 45 The top and bottom 3 layers of jute fiber and a middle double layer of glass fiber exhibited better results in terms of energy absorption, lower damage, and higher compression strength.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the jute fiber/epoxy specimen has the highest damaged area compared to glass fiber/epoxy and carbon fiber/epoxy specimens. The effect of stacking sequence on the low‐velocity impact and compression after impact behavior of glass and jute fiber reinforced hybrid composites was investigated by Pandian et al, 45 The top and bottom 3 layers of jute fiber and a middle double layer of glass fiber exhibited better results in terms of energy absorption, lower damage, and higher compression strength.…”
Section: Introductionmentioning
confidence: 99%
“…26 These days, researchers are more focused on developing hybrid composites as these composites can practically overcome the drawbacks of composites containing only one type of fiber reinforcement. 27,28 For instance, Pndian et al 29 investigated the effect of stacking sequence in polyester reinforced with glass and jute fiber in LVI and CAI tests. According to the obtained results, using multiple reinforcements has played a vital role in increasing the compressive strength after the impact, so the residual compressive strength after the impact of 15 J in the hybrid composite increased by 32.56%.…”
Section: Introductionmentioning
confidence: 99%